Peran Konseling dalam Proses Rehabilitasi Narkoba: Studi Kasus di Lembaga Rehabilitasi Islam Syar’i Narkotika Khalid Bin Walid, Medan - Rahayu Fuji Astuti; Chadiza Auliana Utami; Cici Ramadhani Putri; Sintia Khairiyyahni; Siti Khairuna Salwa Lubis (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the role of counseling in the process of Islamic-based drug rehabilitation at the Khalid Bin Walid Islamic Syar'i Narcotics Rehabilitation Institute, Medan. Using a descriptive qualitative approach, data were collected through semi-structured interviews, observations, and documentation which were then analyzed thematically. The results of the study indicate that individual counseling is the main core in helping participants understand the root of the problem of addiction, build motivation, and design strategies for a healthy, drug-free life. Group therapy complements the rehabilitation process by strengthening solidarity and social skills among participants. In addition, spiritual guidance based on Islamic values plays an important role in strengthening inner peace and commitment to change. However, the rehabilitation process faces significant challenges such as emotional instability of participants, minimal family support, and limited facilities and professional staff. To overcome this, the institution collaborates with various related institutions to support the legal, social, and medical aspects of rehabilitation. This study concludes that drug rehabilitation that integrates an Islamic-based bio-psycho-social-spiritual approach can be an effective model in the recovery of addicts, with the support of synergy between institutions and a conducive social environment.